Perceived harms of and exposure to tobacco use and current tobacco use among reproductive-aged women from the PATH study. Issue 9 (20th October 2020) - Do, Elizabeth K.; Nicksic, Nicole E.; Clifford, James S.; Hayes, Alishia; Fuemmeler, Bernard F.
ABSTRACT: Data for this study were obtained from reproductive-aged women (aged 18–44 years, at wave 1) from waves 1 (2013–2014) and 2 (2014–2015) of the Population Assessment of Tobacco and Health Study ( n = 13, 241). Bivariate and multinomial regression analyses were performed associating past 30-day use of cigarettes only, e-cigarettes only, and dual use with perceptions of harm, exposure to tobacco product use, and sociodemographic variables. Cross-sectional and longitudinal analyses were conducted. Of all reproductive-aged women included in the analyses, 75.5 percent reported no tobacco use, 16.9 percent reported cigarette use only, 1.5 percent reported e-cigarette use only, and 6.1 percent reported dual use within the past 30 days. Perceived harm, tobacco exposure, pregnancy status, age, race/ethnicity, income, education, and sexual orientation were associated with the past 30-day use, cross-sectionally at wave 1. Similar associations were found for longitudinal analyses using wave 2 data, except for income and education, which were no longer associated. The results of this study contribute to knowledge regarding the prevalence and correlates of tobacco use across exclusive cigarette, exclusive e-cigarette, and dual use among reproductive-aged women.